Study of optimization parameters for service chaining in cloud environment - Purohit, Prathamesh; Kadikar, Ruturaj; Susila, M; Amutha, B (International Journal of Engineering and Technology, 2018)
and it is growing towards integration of 5G technology in near future. Therefore, to improve the quality of experience for viewing the content over the internet requires dynamic allocation and adaptation of network resources in an optimized manner. Traditional IP networks are vertically integrated hence flexibility in network resources management is very less. Software-defined networking (SDN) as an emerging technology, which comes with the promise of the solution to dynamically govern various network resources by breaking this chain or hierarchy of vertical integration. Network function virtualization along with service chain optimization provides the solution to enhance the Quality of Experience (QoE) and Quality of Service (QoS). In this paper, we are proposing an approach to improve the QoE by ameliorating the service chain and data center parameters. Â Â